A Problem-Solution Approach - Babin, Lee (Apress, 2012)
PHP has grown over the years and, thanks to its devotees, has continued to adopt the functionality most preferred by its user base. By actually listening to the developers to help guide PHP’s development path, the PHP creators have introduced some impressive function- ality over the years. However, PHP 4, while a sound developmental language and tool, was lacking on a few fronts. For instance, it had a means for developers to take an object-oriented approach, but several key pieces of functionality were not implemented, such as exception handling and session support (for objects). PHP 5 has changed all that. No longer must developers write classes that are missing functionality. Available to PHP is a full set of object-oriented development tools. Of particular note in PHP 5 is the ability to protect class variables in several ways. In addition, inheritance difficulties are now a thing of the past, and exception handling has become a nice way of tak- ing care of pesky errors and validation.